CORAK PENDEKATAN DALAM USHÛL AL-FIQH - Arip Purqon (State Islamic University North Sumatra, 2010)
Abstract: Approaches to Islamic Jurisprudence The Islamic legal theory (ushûl al-fiqh) is one of the most important sciences in the development of Islamic thought used for legal deduction. As a legal theory, the scientific community (‘ulamâ’ al-ûshûl ) has developed a variety of approach to ushûl al-fiqh. This article tires to discuss these approaches which constitute language approach and maqâshid al-syarî‘ah (public goods). The author argues that these two approaches are important means to comprehend how the Islamic jurisprudents deduce law. Linguistic approach is required to understanding the text of the revelation, whereas the maqâshid al-syarî‘ah is needed to consider the very objective of the law as well as to see the values of human interest for every obligation sent down by God. Not denying the importance of language approach, this article put forward the significance of the maqâshid al-syarî‘ah in order to catch God’s messages in the Qur’an.Kata Kunci: pendekatan bahasa, pendekatan maqâshid al-syarî ah, hukum syar‘i